Near-infrared photoactive Ag-Zn-Ga-S-Se quantum dots for high-performance quantum dot-sensitized solar cells - Kottayi, Roopakala; Veerappan, Ilangovan; Sittaramane, Ramadasse (Beilstein Journal of Nanotechnology, 2022)
The high light-harvesting ability of quantum dots (QDs) plays an eminent role in the performance of solar cells. In this study, we synthesized Ag-Zn-Ga-S-Se-based alloyed QDs by colloidal hot injection and characterized them. The X-ray photoelectron spectrum analysis confirms the +1, +2, +3, −2, and −2 oxidation states of, respectively, Ag, Zn, Ga, S, and Se in the QDs, and the energy-dispersive X-ray spectrum analysis confirms the 1:1:1:1.5:1.5 stoichiometric ratio of, respectively, Ag, Zn, Ga, S, and Se. These two results indicate the formation of I-II-III-VI3-type alloyed crystals (AgZnGaS1.5Se1.5 nanocrystals). TEM image analysis reveals the QD nature of the synthesized Ag-Zn-Ga-S-Se nanocrystals. The X-ray diffraction pattern confirms the hexagonal structure. Due to the near-infrared light absorption capability, the synthesized QDs were used as the sensitizer to fabricate QDSCs. The fabricated QDSCs were characterized by using electrochemical impedance spectroscopy and photovoltaic performance studies. The fabricated QDSC have superior electrochemical activity with a photoconversion efficiency of 4.91%.
Keywords: alloyed QDs; photoconversion efficiency; photovoltaic performance; quantum dots